Panties Usage: Feel Comfortable or Sexy? (Human Factors in Design, 2017)
Motivation for panties usage is the main issue of this paper. By means of a survey involving 348 female undergraduate students from two Brazilian universities, we analyzed comfort perception versus appearance evaluation, with an behavioral approach. The study allowed to evaluate the following variables: usage profile (defined by usage frequency); behavioral profile (defined by accordance to any usage situations); comfort perception and appearance evaluation of six models of panties; and dimension of comfort (defined by evaluation of comfort and discomfort descriptors). The analysis involved a clustering of primary data and after that, Crosstables among clusters. Statistical tools we used were K-Means Cluster Analysis and Pearson’s Chi-square Tests by Crosstables with the SPSS8. Results indicated that daring women tend to be extroverted and value psychological comfort; conservative women tend to be introverted and value psychological comfort; moderate women tend to be contextual in usage and doesn’t prioritize any comfort dimension.